Penggunaan Video Animasi Dalam Pembelajaran IPS Guna Untuk Meningkatkan Minat Belajar Siswa Kelas VIII di MTs Miftahul Huda Ngunut Tulungagung - Laviana Aunil Malik; Binti Maunah (Badan Penerbit STIEPARI Press, 2023)
Teaching and learning activities are basically a process of communication carried out between teachers and students, in which both of them exchange ideas. aims to increase students' interest in learning, and to explore this matter more deeply, the researcher formulates the research focus as follows: 1) How is the interest in learning social studies for class VIII students at MTs Miftahul Huda Ngunut Tulungagung, 2) What are the steps for using animated video media in learning, 3) What are the implications of applying animated video media? This research is a research using descriptive qualitative research methods. The location of this research is MTs Miftahul Huda Ngunut Tulungagung. The results of the study are as follows, 1) Students' interest in social studies learning is influenced by the classroom atmosphere and the learning media used. 2) The use of learning media is very necessary in every lesson, 3) The use of animated videos in learning, 4) As a teacher, you have to be creative and innovative. 5) The use of video animation is able to overcome the limitations of the senses, space and time. 6) Animated video media can motivate students to increase student learning interest. 7) The teacher's attention to students with different abilities, both more and less, is of course different, so that all of their students are able to be equal and complete learning well according to the lesson plan standards.